Translation of Passive Voice Found in the Novel The Sea of Monster By Rick Riordan and its Translation By Nuraini Mastura - Widya, Widya; Ayu, Dewi Mutiara Indah (Bina Nusantara University, 2015)
This Present research aims at analyzing the translation of passive voice from English into Indonesian and finding out the problem occurring in translating them. The qualitative descriptive method was applied in this research. The data were gathered from the novel The Sea of Monster by Rick Riordan and its Translation by Nuraini Mastura. The analyzed data were limited, that is, simple present tense, past perfect tense, and modal auxiliary. They are analyzed by applying the semantics and grammatical approaches. The findings have shown that the problems can be either semantic and cultural aspect or grammatical system. Despite those obstacles, it is found that the translator is able to produce a good and natural translation. She can transfer message contained in SL into TL. Cultural context and translation shift are getting involved in the process of creating natural translation.